Seismic-Controlled Blasting Near a Critical Tailings Dam: A Case Study from an Open Pit Copper Mine in Chile - Alejandro Gutierrez; Gabriel Gonzalez; Luis Manriquez; Paulo Couceiro; Juan Navarro (International Society of Explosives Engineers, 2026)
A high-stakes blasting campaign was successfully executed at a major open pit copper mine in northern Chile. This operation posed a significant technical challenge due to its immediate proximity to the tailings dam - a critical infrastructure whose structural integrity depends on strict control of blast-induced seismic vibrations. The geological complexity of the area, characterized by upper andesite interbedded with caliche (carbonate), further complicated the operation. This lithological composition, known for its high tenacity and cohesion, posed additional challenges for achieving effective fragmentation, necessitating a highly customized blast design and loading strategy. The campaign included four production blasts and one secondary blast, all executed under the constraint of not exceeding the Peak Ground Acceleration (PGA) threshold of 0.64g, as defined by the Maximum Credible Earthquake (MCE) scenario. To ensure compliance, geophones were strategically installed at three monitoring points (P1, P2, and P3) on the dam to capture real-time acceleration data. The use of specialized blast patterns, precise stemming control, and electronically sequenced detonations ensured that all recorded accelerations remained well below the critical threshold. A total of 496,163 tonnes of material were safely blasted, with 8,452 meters drilled and powder factors ranging from 419 to 594 g/ton. Therefore, this case study exemplifies operational excellence in controlled blasting, demonstrating the feasibility of safe mining near geotechnically sensitive zones through predictive modeling, rigorous QA/QC, and post-blast analysis.